Synthesis of Ca(OH)2 and Na2CO3 through anion exchange between CaCO3 and NaOH: effect of reaction temperature. Issue 49 (11th November 2022) - Simoni, Marco; Hanein, Theodore; Woo, Chun Long; Nyberg, Magnus; Tyrer, Mark; Provis, John L.; Kinoshita, Hajime
Abstract : The chemical decarbonisation of CaCO3 was successfully tested in a range of mild temperatures simulating those oscillations occurring within processes, and the kinetic parameters were gained. Abstract : The CO2 released upon calcination of limestone accounts for the largest portion of the emissions from the cement, lime, and slaked lime manufacturing industries. Our previous works highlighted the possibility for a no-combustion decarbonisation of CaCO3 through reaction with NaOH solutions to produce Ca(OH)2 at ambient conditions, while sequestrating the process CO2 in a stable mineral Na2 CO3 ·H2 O/Na2 CO3 . In this study, the effect of temperature was assessed within the range of 45–80 °C, suggesting that the process is robust and only slightly sensitive to temperature fluctuations. The proportioning of the precipitated phases Na2 CO3 ·H2 O/Na2 CO3 was also assessed at increasing NaOH molalities and temperatures, with the activity of water playing a crucial role in phase equilibrium. The activation energy ( E a ) of different CaCO3  : NaOH : H2 O systems was assessed between 7.8 kJ·mol −1 and 32.1 kJ·mol −1, which is much lower than the conventional calcination route. A preliminary energy balance revealed that the chemical decarbonisation route might be ∼4 times less intensive with respect to the thermal one. The present work offers a further understanding of the effect of temperature on the process with the potential to minimise the emissions from several energy-intensive manufacturing processes, and correctly assess eventual industrial applicability.